High-risk histopathological features of retinoblastoma following primary enucleation: A Global Study Of 1,426 Patients From 5 Continents - Kaliki, Swathi (2024)
Purpose: To evaluate high-risk histopathological features following primary enucleation of eyes with retinoblastoma and assess the patient outcomes across continents. Methods: A retrospective study of 1,426 primarily enucleated retinoblastoma eyes from five continents. Results: Of all, 923 (65%) were from Asia (AS), 27 (2%) from Australia (AUS), 120 (8%) from Europe (EUR), 162 (11%) from North America (NA), and 194 (14%) from South America (SA). Based on the continent (AS vs. AUS vs. EUR vs. NA vs. SA), the histopathological features included massive choroidal invasion (31% vs. 7% vs. 13% vs. 19% vs. 27%, P = 0.001), postlaminar optic nerve invasion (27% vs. 0% vs. 16% vs. 21% vs. 19%, P = 0.0006), scleral infiltration (5% vs. 0% vs. 4% vs. 2% vs. 7%, P = 0.13), and microscopic extrascleral infiltration (4% vs. 0% vs. <1% vs. <1% vs. 4%, P = 0.68). Adjuvant chemotherapy with/without orbital radiotherapy was given to 761 (53%) patients. Based on Kaplan-Meier estimates in different continents (AS vs. AUS vs. EUR vs. NA vs. SA), the 6-year risk of orbital tumor recurrence was 5% versus 2% versus 0% versus 0% versus 12% (P < 0.001), systemic metastasis was reported in 8% versus 5% versus 2% versus 0% versus 13% (P = 0.001), and death in 10% versus 3% versus 2% versus 0% versus 11% (P < 0.001) patients. Conclusion: There is a wide variation in the infiltrative histopathological features of retinoblastoma across continents, resulting in variable outcomes. SA and AS had a higher risk of orbital tumor recurrence, systemic metastasis, and death compared to AUS, EUR, and NA.